2010
DOI: 10.1007/s00210-010-0522-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginsenoside Rg2 on the ultraviolet B-induced DNA damage responses in HaCaT cells

Abstract: Our previous study demonstrated the increase in the repair of UVB damage by mRg2, a mixture of ginsenosides containing 60% Rg2 in NIH3T3 cells. In the present study, the effects of purified Rg2 on the repair and apoptosis in ultraviolet B (UVB)-exposed HaCaT cells were investigated on gene expression levels. When cells were exposed to UVB and post-incubated in normal medium for 24 h, the cell viability decreased to about 50% of that in nontreated control. When Rg2 was post-incubated, however, the UVB-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Our previous studies have suggested that these decreases are associated with the repair of the UVB-induced DNA damage accompanied by the accelerated p53 and GADD45 expression at earlier time periods (Jeong et al 2007;Ha et al 2010). In the present study, we also observed the Rg2-mediated protection from UVB damage in control siRNA-transfected cells, but not in p53 knockdown cells (Figures 2-5).…”
Section: Resultssupporting
confidence: 73%
“…Our previous studies have suggested that these decreases are associated with the repair of the UVB-induced DNA damage accompanied by the accelerated p53 and GADD45 expression at earlier time periods (Jeong et al 2007;Ha et al 2010). In the present study, we also observed the Rg2-mediated protection from UVB damage in control siRNA-transfected cells, but not in p53 knockdown cells (Figures 2-5).…”
Section: Resultssupporting
confidence: 73%
“…The up-regulation of p53 signalling intermediates, including GADD45, has been reported in human promyelocytic leukemia cells exposed to volatile organic compounds, such as benzene and toluene, suggesting that the responses of p53 pathways to genotoxic and non-genotoxic agents are disparate and complex [33]. A number of small molecules that act upstream of p53 or target the p53 protein itself to rescue p53 function have been identified recently [34].…”
Section: Resultsmentioning
confidence: 99%
“…Postincubation of the UVB-exposed cells in a medium containing ginsenoside Rg2 significantly reduced UVB-induced DNA damage responses in HaCaT cells (34). Obvious protective effects of ginsenoside Rg1 and Rb1 can be observed against UVB radiation-induced HaCaT cells' nucleolus damage (14).…”
Section: Discussionmentioning
confidence: 99%